Hepatocellular carcinoma after direct‐acting antivirals for hepatitis C is associated with KIR‐HLA types predicting weak NK cell‐mediated immunity - Ryan, James C.; Haight, Christina; Niemi, Erene C.; Grab, Joshua D.; Dodge, Jennifer L.; Lanier, Lewis L.; Monto, Alexander (European journal of immunology, 2024)
Background and aims Second‐generation direct‐acting antivirals (2G DAA) to cure HCV have led to dramatic clinical improvements. HCV‐associated hepatocellular carcinoma (HCC), however, remains common. Impaired immune tumor surveillance may play a role in HCC development. Our cohort evaluated the effects of innate immune types and clinical variables on outcomes including HCC. Methods Participants underwent full HLA class I/KIR typing and long‐term HCV follow‐up. Results A total of 353 HCV+ participants were followed for a mean of 7 years. Cirrhosis: 25% at baseline, developed in 12% during follow‐up. 158 participants received 2G DAA therapy. HCC developed without HCV therapy in 20 subjects, 24 HCC after HCV therapy, and 10 of these after 2G DAA. Two predictors of HCC among 2G DAA‐treated patients: cirrhosis (OR, 10.0, p = 0.002) and HLA/KIR profiles predicting weak natural killer (NK) cell‐mediated immunity (NK cell complementation groups 6, 9, 11, 12, OR of 5.1, p = 0.02). Without 2G DAA therapy: cirrhosis was the main clinical predictor of HCC (OR, 30.8, p < 0.0001), and weak NK‐cell‐mediated immunity did not predict HCC. Conclusion Cirrhosis is the main risk state predisposing to HCC, but weak NK‐cell‐mediated immunity may predispose to post‐2G DAA HCC more than intermediate or strong NK‐cell‐mediated immunity. In patients with hepatitis C cirrhosis who are treated with 2G DAA, predicted weak NK‐cell‐mediated immunity may predispose to HCC development more than predicted intermediate or strong NK‐cell‐mediated immunity.